Health and Children with Disabilities - Megan MacDonald (Frontiers Research Topics, 2017)
Articles within this e-book are focused on the health of children with disabilities. Various frameworks have been used to articulate the dynamic interaction of the individual, environment and the task as it relates to child health. A majority of the contributing authors in this special topic are researchers within the field of adapted physical activity. This field embraces a broad perspective of inclusiveness and attitudes of acceptance.